Extending the phenotypic spectrum of RBFOX1 deletions: Sporadic focal epilepsy. (15th July 2015) - Lal, Dennis; Pernhorst, Katharina; Klein, Karl Martin; Reif, Philipp; Tozzi, Rossana; Toliat, Mohammad R.; Winterer, Georg; Neubauer, Bernd; Nürnberg, Peter; Rosenow, Felix; Becker, Felicitas; Lerche, Holger; et al.
Summary Partial deletions of the RBFOX1 gene encoding the neuronal splicing regulator have been reported in a range of neurodevelopmental diseases including idiopathic/genetic generalized epilepsy (IGE/GGE), childhood focal epilepsy, and self‐limited childhood benign epilepsy with centrotemporal spikes (BECTS, rolandic epilepsy), and autism. The protein regulates alternative splicing of many neuronal transcripts involved in the homeostatic control of neuronal excitability. Herein, we examined whether structural deletions affecting RBFOX1 exons confer susceptibility to common forms of juvenile and adult focal epilepsy syndromes. We screened 807 unrelated patients with sporadic focal epilepsy, and we identified seven hemizygous exonic RBFOX1 deletions in patients with sporadic focal epilepsy (0.9%) in comparison to one deletion found in 1, 502 controls. The phenotypes of the patients carrying RBFOX1 deletions comprise magnetic resonance imaging (MRI)–negative epilepsy of unknown etiology with frontal and temporal origin (n = 5) and two patients with temporal lobe epilepsy with hippocampal sclerosis. The epilepsies were largely pharmacoresistant but not associated with intellectual disability. Our study extends the phenotypic spectrum of RBFOX1 deletions as a risk factor for focal epilepsy and suggests that exonic RBFOX1 deletions are involved in the broad spectrum of focal and generalized epilepsies.